Patient‐derived xenografts for individualized care in advanced sarcoma. Issue 13 (4th April 2014) - Stebbing, Justin; Paz, Keren; Schwartz, Gary K.; Wexler, Leonard H.; Maki, Robert; Pollock, Raphael E.; Morris, Ronnie; Cohen, Richard; Shankar, Arjun; Blackman, Glen; Harding, Victoria; Vasquez, David; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Patients with advanced, metastatic sarcoma have a poor prognosis, and the overall benefit from the few standard‐of‐care therapeutics available is small. The rarity of this tumor, combined with the wide range of subtypes, leads to difficulties in conducting clinical trials. The authors previously reported the outcome of patients with a variety of common solid tumors who received treatment with drug regimens that were first tested in patient‐derived xenografts using a proprietary method ("TumorGrafts"). METHODS Tumors resected from 29 patients with sarcoma were implanted into immunodeficient mice to identify drug targets and drugs for clinical use. The results of drug sensitivity testing in the TumorGrafts were used to personalize cancer treatment. RESULTS Of 29 implanted tumors, 22 (76%) successfully engrafted, permitting the identification of treatment regimens for these patients. Although 6 patients died before the completion of TumorGraft testing, a correlation between TumorGraft results and clinical outcome was observed in 13 of 16 (81%) of the remaining individuals. No patients progressed during the TumorGraft‐predicted therapy. CONCLUSIONS The current data support the use of the personalized TumorGraft model as an investigational platform for therapeutic decision‐making that can guide treatment for rare tumors such as sarcomas. A randomized phase 3 trial versus physician's choice is warranted. Cancer 2014;120:2006–2015. © 2014 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society.